Empowering Local Tourism through Competitive Swimming Events for Sustainable Development at Swembath Natural Springs - Tulus; Marpaung, T.J.; Lubis, Andrew Satria; Marpaung, Nicholas; Marpaung, Jonathan Liviera (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This article presents the results of a community empowerment project aimed at revitalizing local tourism at Swembath Natural Springs in Naga Soppa, Simalungun Regency, North Sumatra. Faced with declining visitor numbers and the need to boost local economic activity, this project integrated competitive swimming events as a new attraction while fostering sustainable development. The construction of an international-standard swimming pool served as the foundation for this initiative, offering a venue for sports tourism that attracts both athletes and recreational visitors. The project also included comprehensive training for local businesses, focusing on tourism management, digital marketing, and service improvement, thereby empowering the community to capitalize on the influx of tourists. The results show a significant increase in visitor numbers during swimming competitions, positively impacting local businesses such as food vendors, craft sellers, and accommodation providers. Moreover, the project fostered environmental conservation efforts, ensuring that the natural beauty of Swembath is preserved for future generations. This initiative aligns with Sustainable Development Goals (SDGs), particularly in terms of economic empowerment and environmental sustainability. The community now possesses the tools and infrastructure needed to maintain Swembath as a competitive tourist destination, with a sustainable model that benefits both the environment and the local economy. The project's success highlights the potential of integrating sports tourism and community-based empowerment to foster long-term economic growth and environmental stewardship.